2020
DOI: 10.1093/biolre/ioaa135
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral action of kisspeptin at reproductive tissues—role in ovarian function and embryo implantation and relevance to assisted reproductive technology in livestock: a review

Abstract: Kisspeptin (KISS1) is encoded by the KISS1 gene and was initially found to be a repressor of metastasis. Natural mutations in the KISS1 receptor gene (KISS1R) were subsequently shown be associated with idiopathic hypothalamic hypogonadism and impaired puberty. This led to interest in the role of KISS1 in reproduction. It was established that KISS1 had a fundamental role in the control of GnRH secretion. KISS1 neurons have receptors for leptin and estrogen receptor α (ERα) which places KISS1 at the gateway of m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 206 publications
(106 reference statements)
0
17
0
3
Order By: Relevance
“…The vital role of the endometrial layer in the control of uterine contractility was already demonstrated by the local production of different agents affecting smooth muscle function (Kothencz et al, 2018). A networking is already proved with kisspeptin neurons in the central nervous system (Arthur et al, 2008) and the reproductive organs (D'Occhio et al, 2020), but no data is available for the uterine smooth muscle in this respect.…”
Section: Discussionmentioning
confidence: 99%
“…The vital role of the endometrial layer in the control of uterine contractility was already demonstrated by the local production of different agents affecting smooth muscle function (Kothencz et al, 2018). A networking is already proved with kisspeptin neurons in the central nervous system (Arthur et al, 2008) and the reproductive organs (D'Occhio et al, 2020), but no data is available for the uterine smooth muscle in this respect.…”
Section: Discussionmentioning
confidence: 99%
“…Kisspeptin neurons which are located in the hypothalamus as with GnRH neurons are recognized to orchestrate the hypothalamus-pituitary-gonadal (HPG) axis, a robust mechanism for the regulation of reproduction both in male and female mammals 46 48 . As the main regulatory clock, the SCN, is controlled by the light–dark cycle 12 , but the circadian rhythms of peripheral tissues deviate from the SCN cycle due to insulin/IGF1-mediated feeding and fasting cycles 17 , 18 , our analysis was focused on the displacement of circadian rhythms in peripheral tissues such as ovary.…”
Section: Discussionmentioning
confidence: 99%
“…The nidation depends on the degree of trophoblast infiltration into the uterine extracellular matrix where kisspeptin combined with other proinflammatory cytokines, notably tumor necrosis factor-alpha, blocks invasion by stimulating apoptosis [ 5 ]. As a result, KISS1 plays a part in controlling the rate of syncytiotrophoblast cell invasion and angiogenesis, ensuring that early placentation occurs in a controlled and sequential manner [ 30 ]. Moreover, KISS1R and GPR54 are predominantly expressed in the trophoblast of the first-trimester placenta, where the invasive capacity is at its highest.…”
Section: Reviewmentioning
confidence: 99%
“…Moreover, KISS1R and GPR54 are predominantly expressed in the trophoblast of the first-trimester placenta, where the invasive capacity is at its highest. On the contrary, KISS1R and GPR54 are poorly expressed in the full-term gestation placenta [ 30 ]. We can deduce that KISS1 has a similar part in the inhibition of cell migration in both early pregnancy and tumor metastasis [ 30 ].…”
Section: Reviewmentioning
confidence: 99%
See 1 more Smart Citation